Impact of omalizumab in children from a middle‐income country with severe therapy‐resistant asthma: A real‐life study. Issue 11 (13th October 2017) - Pitrez, Paulo M.; de Souza, Rodrigo G.; Roncada, Cristian; Heinzmann‐Filho, Joao P.; Santos, Giovana; Pinto, Leonardo A.; Jones, Marcus H.; Stein, Renato T.
Abstract: Background: Severe asthma in children is a global health problem. Severe therapy‐resistant asthma (STRA) in children is a major clinical challenge due to persistent symptoms despite high doses of corticosteroids and results in high public health costs. Omalizumab (anti‐IgE monoclonal antibody) has been described as an effective add‐on therapy in these patients. The characteristics of children with STRA from low‐ and middle‐income countries have scarcely been reported, and no real‐life study has been published on the effects of omalizumab in this group of patients. The aim of our study is to report the first clinical real‐life experiences with omalizumab in Brazilian children with STRA. Methods: Children (6‐18 years old) from a referral center who were diagnosed with STRA were included in this retrospective study based on our clinical databases. The included children had undergone at least 6 months of omalizumab treatment and fulfilled the following initial criteria: 1) >6 years old; 2) a positive skin‐prick test for at least one aeroallergen; and 3) a serum total IgE level between 30 and 1500 IU/mL. Clinical and lung function variables were analyzed before and after treatment. Results: Fourteen children (mean age: 11.9 years; percentage female: 72%) were included in this study. Omalizumab treatment significantly increased control of the disease according to a standardized questionnaire administered at every visit ( P  < 0.0001), ceased hospitalizations in 70% ( P  = 0.02) of patients, and allowed 8/9 (89%) patients to be weaned off oral steroids ( P  = 0.004). Conclusions: In this retrospective report, the use of omalizumab in Brazilian children with STRA significantly improved disease control, decreased hospitalizations, and allowed suspension of continuous oral corticosteroids.